Viết các biểu thức sau dưới dạng tổng

Question

Viết các biểu thức sau dưới dạng tổng
viet-cac-bieu-thuc-sau-duoi-dang-tong

in progress 0
Kiệt Gia 8 tháng 2020-10-16T19:34:43+00:00 2 Answers 101 views 0

Answers ( )

  1. Đáp án:

     

    Giải thích các bước giải :

    c.1 $( \frac{1}{2} – x )^{2}$

    = ($\frac{1}{2}$ – x)($\frac{1}{2}$ -x)

    = $\frac{1}{2}$ ($\frac{1}{2}$ – x ) – x ( $\frac{1}{2}$ – x )

    = $\frac{1}{4}$ – $\frac{1}{2}$x – $\frac{1}{2}$x + $x^{2}$

    = ($\frac{1}{4}$ -x )+ $x^{2}$

    c.2) $(2x-1)^{2}$

    = (2x-1)(2x-1)

    = 2x(2x-1)-(2x-1)

    = 4$x^{2}$ – 2x – 2x + 1

    = ( 4$x^{2}$ – 4x )+ 1

    d.1)$(2x-3y)^{2}$

    = (2x-3y)(2x-3y)

    = 2x(2x-3y) – 3y(2x-3y)

    = 4$x^{2}$ – 6xy – 6xy + 9$y^{2}$

    =( 4$x^{2}$ – 12xy )+ 9$y^{2}$

    d.2)$(0,01-xy)^{2}$

    = (0,01 – xy) ( 0,01 – xy )

    = 0,01(0,01-xy)-xy(0,01-xy)

    = 0,0001 – 0,01xy – 0,01xy + $x^{2}$ $y^{2}$

    =( 0,0001 – 0,02xy )+ $x^{2}$ $y^{2}$

    g) (x+y+z).(x-y-z)

    = x(x-y-z) + y(x-y-z) + z(x-y-z)

    = $x^{2}$ – xy – xz + xy – $y^{2}$ – yz + xz – yz – $z^{2}$

    = $x^{2}$ – $y^{2}$ – $z^{2}$

    h) (x-y+z) ( x+y+z )

    = x (x-y+z) + y(x-y+z) + z(x-y+z)

    = $x^{2}$ – xy + xz + xy – $y^{2}$ + yz + xz – yz + $z^{2}$

    = $x^{2}$ – $y^{2}$ + $z^{2}$ + 2xz

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )